Bulan Imunisasi Anak Nasional: Imunisasi Penting Untuk Kekebalan dan Cegah Stunting - Edo Aprianto; Hilton Tarnama (FKM UIN Sumatera Utara Medan, 2022)
The problem of stunting in Indonesia is a serious threat that requires appropriate treatment to overcome developmental disorders in children caused by poor nutrition, repeated infections, and inadequate psychosocial simulation. The Stunting Reduction Program to 14% in 2024 is a program for the government and the people of Indonesia in the midst of this pandemic. Moreover, the activities at the Integrated Service Post (Posyandu) as the main milestone for monitoring the growth and development of toddlers in a smaller area are seen to be less than optimal. Economic conditions in Indonesia during the pandemic showed that poverty and unemployment rates were increasing, thus affecting the increase in the prevalence of stunting in Indonesia, this is because a person's economic condition affects the nutritional intake and nutrition he gets. The incidence of stunting in those who were not immunized was doubled compared to those who were fully immunized. In complete immunization about 10%, which is not immunized 21.1%. This shows that there is a relationship between immunization and stunting. The basic contribution of this program is the transfer of knowledge and the success of the National Child Immunization Month to reduce the number of stunting in Pandeglang Regency. The method of implementation is through three stages, namely the preparation stage and the implementation stage, as well as the evaluation stage. The preparation stage is the stage of preparing all data on children receiving immunizations and mothers as the main actors in preventing stunting. The implementation stage is in the form of immunization and health education regarding Stunting Prevention with the Success of National Child Immunization Month. Then, the evaluation stage becomes the final stage which examines deficiencies both in pre and post activities. The conclusion from community service is that the high stunting rate can be reduced by immunization.